Leo XIV and the cultural bankruptcy of the Catholic Church - Jesús Enciso González, Jesús (2025)
With almost two millennia of existence, the Catholic Church is one of the longest-standing and most complex institutions in Western civilisation. Its history has been marked by periods of expansion and consolidation, as well as moments of profound crisis that have required it to rethink its horizons of expectation, allowing it to build remarkable historical resilience, which, in turn, means its continuity and capacity for renewal. One of the most significant responses to these crises has been the convening of ecumenical councils, which we understand as privileged spaces for ecclesial discernment, where both current issues and structural challenges are addressed. In the current context, under the leadership of Pope Leo XIV, there is an urgent need for theological reflection that, without losing sight of fidelity to tradition, is capable of critically engaging with contemporary challenges and opening paths for the future of the Church. This article focuses precisely on this cultural dimension, understood as an anthropological horizon from which both the forms of living the faith and the models of authority and transmission of the Catholic tradition are configured.